The ruptures caused by COVID 19 and the International Relations - Méndez-Coto, Marco Vinicio (2020)
The arrival of COVID19 transformed our understanding of the “normality” in our lives, raising questions about whether there will be a return to a previous stage, or whether we should expect a new form of coexistence. From the perspective of International Relations, COVID 19 as the global threat that has shaped 2020, can be framed within three major fractures or ruptures. The first between the individual-collective, with the resurgence of the modern State and the restitution of the internal-external division constructed with the borders, and the alleged control within the State jurisdiction.  The second is between inclusion-exclusion, or between "us" and "them", with the stigmatization of the foreigner and the closing of borders; when people is seen as a suspects due to their ethnic origin; as well as the division constructed by the social or class structure. The third among winners and losers from an International Political Economy perspective.